Cerebral/Cortical visual impairment (CVI) in Down syndrome: a case series - Boatwright, Elizabeth; Banihani, Rudaina; Willems, Ilse; Lehman, Kathleen; Mazel, Ellen; Mark, Hannah; Wong, Mike; Vietzman, Silvia; Chandna, Arvind; Heidary, Gena; , DSMIG DS+CVI Workgroup (Frontiers in Human Neuroscience, 2025)
Cerebral/Cortical visual impairment (CVI), a brain-based visual condition, is a leading cause of childhood blindness and low vision but remains underdiagnosed in individuals with Down syndrome (DS). This report presents three case studies of adolescents with DS and CVI (DS + CVI), illustrating how CVI can manifest alongside the developmental, cognitive, behavioral, and social profiles of individuals with DS. We describe comprehensive ophthalmological evaluations, assessment for visual perceptual deficits with a screener questionnaire, functional vision assessments, and neuroimaging (when available). Through a detailed retrospective examination of these cases, we explore the complex interplay between CVI and DS, emphasizing how CVI-related challenges—such as difficulties with visual attention, spatial perception, processing, and navigation—are often misattributed to DS alone or to other more commonly recognized co-occurring conditions in DS. Diagnostic overshadowing, coupled with a lack of standardized screening tools, has led to delayed diagnoses and missed opportunities for intervention. Our findings highlight the importance of recognizing CVI in individuals with DS using reliable tools for assessment of functional vision to better appreciate the effect on their diverse developmental outcomes, and to incorporate CVI into our understanding of the DS phenotype. These case reports underscore the need for further research to determine the prevalence and impact of CVI in DS and advocate for the development of tailored screening protocols and evidence-based interventions to support individuals with DS + CVI across the lifespan.